PERANAN KEPEMIMPINAN DALAM MENINGKATKAN DISIPLIN KERJA PEGAWAI NEGERI SIPIL DI BALAI PENGKAJIAN TEKNOLOGI PERTANIAN (BPTP) SULAWESI UTARA - Nagara, Laurencia; Tulusan, Femmy; Pombengi, Jericho (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract :leader plays a very strategic. Success or failure of the public bureaucracy carrying out his dutiesvery determined quality leaders. Therefore, the position of the leader dominates all activities undertaken.For the purpose of this study determine Leadership Role in improving Discipline Work at Institute forAgricultural Technology (BPTP) North Sulawesi.This research uses qualitative research is research that is used to examine the condition of natural objectsin which the researcher is a key instrument. Data collection techniques triangulation done. Thepopulation in this study is the one on the overall employee is an employee at the Institute for AgriculturalTechnology (BPTP) North Sulawesi numbered 97 people.The results showed leadership role which is run by the head of the Ministry of Agriculture as a whole cansay, not maximum, at first review the terms of influence. In terms of regulatory discipline, time and theduties and responsibilities of the employees so far is far from goodKeywords: Leadership, Discipline Work